The Impact of the Communist Regime in Albania on Freedom of Religion for Albanians - Tokrri, Renata; Tafani, Ismail; Shkembi, Aldo (Richtmann Publishing, 2021)
The multi religions Albania passed last century from a country where atheism was the constitutional principle in a country where the basic card guarantees not only the freedom of religion but also the freedom from religion. Today, in order of guaranteeing the freedom of belief, the Constitution of Republic of Albania expresses principles which protect the religious freedom, starting from its preamble. Indeed, the preamble has no legal force but stated goals and assists in the interpretation of provisions. The spirit, with which the preamble stated, is that of tolerance and religious coexistence, in a vision where the people are responsible for the future with faith in God or other universal values. This statement reinforces the principle of secularism of the state where the latter appears as the guarantor of religious freedom by knowing in this perspective the beliefs that